The factors affecting neurogenesis after stroke and the role of acupuncture - Mu, Jie-Dan; Ma, Liang-Xiao; Zhang, Zhou; Qian, Xu; Zhang, Qin-Yong; Ma, Ling-Hui; Sun, Tian-Yi (Frontiers in Neurology, 2023)
Stroke induces a state of neuroplasticity in the central nervous system, which can lead to neurogenesis phenomena such as axonal growth and synapse formation, thus affecting stroke outcomes. The brain has a limited ability to repair ischemic damage and requires a favorable microenvironment. Acupuncture is considered a feasible and effective neural regulation strategy to improve functional recovery following stroke via the benign modulation of neuroplasticity. Therefore, we summarized the current research progress on the key factors and signaling pathways affecting neurogenesis, and we also briefly reviewed the research progress of acupuncture to improve functional recovery after stroke by promoting neurogenesis. This study aims to provide new therapeutic perspectives and strategies for the recovery of motor function after stroke based on neurogenesis.